Implementation of the Iqra'-Imla' Method in Improving the Ability to Read and Write the Qur'an at Al-Khairaat Tompe Middle School - Moh. Afif Algifarri; Fatimah Saguni (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to improve students' ability to read and write the Qur'an through the application of the combined Iqra'-Imla' method at MTs Al-Khairaat Tompe. The background of the study shows that most students still have difficulty pronouncing the hijaiyah letters correctly, understanding the rules of tajweed, and writing Arabic letters correctly. The Iqra' method focuses on the skill of reading the Qur'an gradually and systematically, while the Imla' method emphasizes the skill of writing Arabic letters through dictation exercises. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, reading and writing ability tests, and documentation. The results of the study showed a significant increase after the application of the combined method. The average score for reading the Qur'an increased from 55 to 78, while the skill of writing Arabic letters increased from 50 to 80. Student responses were also positive, seen from increased motivation, self-confidence, and discipline in learning. Thus, the Iqra'-Imla' method is proven to be effective in improving students' Qur'an literacy and is relevant to be applied in Islamic Religious Education learning.